The Impact of Leadership Style on Company’s Performance in the Automobile Painting and Moulding Sector in Maharashtra State of India - Deore, Nandkishor (Global journal of Business and Integral Security, 2024)
Performance of organizations is related to the profitability of the organizations in terms of its growth and profit both in long and short term. In business organizations, investors and businessmen desire and endeavor to ensure that their organizations perform well to earn more profit, grow fast and achieve competitive edge in the industry. In the global competitive environment effective leadership style is necessary to reduce the business losses and proper resource utilization. For organizations to perform well, apart from tangible and intangible resources, effective and dynamic leadership is a pre requisite. If the basis leadership concept and attitude towards work is not up to the mark eventually it will affect organizational goal productivity. It will not only hamper the productivity but also the performance of productivity. Though most of the researchers in the past agreed that leadership style has relationship with organizational performance but there are some who did not support this view, hence, an ambiguity exists. To address this confusion, the researchers studied the types/styles of leadership and the leadership styles of different leaders of various organizations in India and examined their impact on organizational performance. There are three main leadership styles; transformational, transactional and laissez faire leadership styles. While the first two have a positive but different level of impact, the third one has a negative impact on organizational performance. The research also describes the performance of the organizations in service sector because of the good leadership qualities. The basic objective of the present study is to study the role of leadership characteristics on organizational performance. Therefore, the prime agenda of the research study is, how leadership behavior is directly proportional to organizational performance. A quantitative study was conducted by using a questionnaire filled from various leaders of manufacturing and service organizations. Results of the study found that though the most suited style of leadership is transformational one but in new and growing organizations transactional leadership style may be more productive, while in certain circumstances though limited and for a short period, laissez faire style may be required. Hence, the leader might have to adopt a hybrid style of leadership style. Leadership style has a significant impact on the organizational performance.